2020
DOI: 10.1016/j.arth.2019.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Biomechanical Differences Between Condylar Constrained Knee and Rotating Hinged Implants: A Numerical Study

Abstract: Background: Different levels of constraint for total knee arthroplasty can be considered for revision surgeries. While prior studies have assessed the clinical impact and patient outcomes of condylar constrained knee (CCK) and rotating hinged (RTH) implants, nowadays little is known about the biomechanical effects induced by different levels of constraint on bone stress and implant micromotions. Methods: CCK and RTH implant models were analyzed using a previously validated numerical model. Each system was inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…7,[18][19][20] A recent biomechanical study has compared the bone stresses and implant micromotions of a HTKA to FSTKA prosthesis. 21 This study has demonstrated that HTKA prostheses have the highest implant to bone stress, especially at the tip of the stems. This could explain the mechanism for the higher periprosthetic fracture rate seen with these implants.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…7,[18][19][20] A recent biomechanical study has compared the bone stresses and implant micromotions of a HTKA to FSTKA prosthesis. 21 This study has demonstrated that HTKA prostheses have the highest implant to bone stress, especially at the tip of the stems. This could explain the mechanism for the higher periprosthetic fracture rate seen with these implants.…”
Section: Discussionmentioning
confidence: 86%
“…The reasons for the increased periprosthetic fracture risk with HTKA prosthesis remains uncertain, although this complication has been noted in other small case series of HTKA prostheses 7,18–20 . A recent biomechanical study has compared the bone stresses and implant micromotions of a HTKA to FSTKA prosthesis 21 . This study has demonstrated that HTKA prostheses have the highest implant to bone stress, especially at the tip of the stems.…”
Section: Discussionmentioning
confidence: 95%
“…We have reported high survivorship at ten years, in keeping with contemporary literature. In their recent biomechanical study comparing stresses of constrained condylar knee (CCK) with rotating-hinge implants, Andreani et al 24 reported interesting findings where rotating-hinge implant induced high stress compared to the CCK, especially in the region close to tip of the stem. However, higher stresses in the proximal tibia were seen with CCK implant due to the post-cam system, leading to higher implant micromotions due to greater torsional constraint.…”
Section: Discussionmentioning
confidence: 99%
“…All the steps used for the development of the model, from geometry definition, material models and properties, loads, boundary conditions, and mesh, were performed in strict agreement with the previously validate finite element model [ 22 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…A cobalt-chromium alloy (CoCr), a titanium alloy (Ti-6Al-4V), and an ultra-high-molecular-weight-polyethylene (UHMWPE) were respectively used for the femoral component, tibial tray, and tibial insert; as with the previous study, homogeneous isotropic models were selected for these materials [ 16 , 17 , 43 ] and their properties were the following: for CoCr: E = 220 GPa, ν = 0.3 [ 25 , 32 ]; for titanium: E = 117 GPa, ν = 0.3 [ 30 , 35 ]; and for UHMWPE: E = 0.685 GPa, ν = 0.4 [ 28 , 30 , 40 , 42 ].…”
Section: Methodsmentioning
confidence: 99%